Peran Dukungan Keluarga dalam Membangun Work-Family Balance dan Mengatasi Stres Pengasuhan Ibu Bekerja - Annisa Rahmadhani; Astrid Nabillah; Kamila Nisrina Firdaus; Isnaeni Najmal Hakim; Elvaretta Aurel Hidayat; Fina Idamatussilmi; Yani Achdiani; Sarah Nurul Fatimah (Badan Penerbit STIEPARI Press, 2025)
This study aims to identify effective forms of family support in helping working mothers balance multiple roles and reduce parenting stress. The method used was a literature study, which involved analysis of data from various sources to produce clearer conclusions and focus on issues relevant to the topic of work-family balance and focus on issues relevant to the topic of work-family balance, family support, and parenting stress. The results of the study showed that open family communication, equitable division of household tasks, as well as emotional and practical support from family members are important factors in building work-family balance. These strategies help mothers reduce stress and improve psychological well-being. This research recommends the development of family communication training, flexible work policies, as well as further qualitative-based research to explore working mothers' the direct experiences of working mothers. The findings are expected to serve as a basis for development of programs and policies that support the dual role of mothers in the family and workplace.